Pengaruh Kompetensi Guru dan Beban Kerja Terhadap Kinerja Guru di SMP Negeri 150 pada Saat Pandemi Covid-19 - Niken Gayatri Puteri; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
This research is aimed to know if there are any influences between teacher competency and workload on the teacher performance at the SMP Negeri 150 during the Covid-19 pandemic. This study uses a quantitative approach by distributing questionnaires to 51 teachers. The sampling technique is purposive sampling. This research uses validity test, reliability test, classical assumption test, hypothesis test, and multiple regression test and is processed using the IBM SPSS Statistic 20 program. The results of this study indicate that the teacher competency variable has an affect on teacher performance. Workload affects teacher performance. Teacher competency and workload affect teacher performance.